Analysis of Arabica Coffee Production Trend and Major Production Constraints in East and West Hararghe Zones, Ethiopia - Hailu, Addisu; Wako, Kedir (Directorate of Research and Community Services, 2024)
This assessment was designed to generate relevant information on coffee production trends and major production and marketing constraints and to provide sufficient information and analytics for future coffee production. Focus group discussions and key informant interviews were used for primary data collection. Secondary data was collected from the Zones and Districts Bureau of Agriculture; a literature review was used for the data analysis, and pairwise ranking and the graph were used. The major coffee production and marketing constraints were disease and insect pests, poor agronomic management, land shortage, moisture stress, lack of improved varieties, extension and structure, and absence of incentives/subsidies. The major coffee marketing constraints were the lack of stable and fair market prices, involvement of illegal traders, lack of price incentives for quality production, and traders mixing Hararghe coffee with another place. Overall indicators of coffee production status and volume supplied to the national market do not show a positive trend with critical challenges/constraints. Hence, strategic and systematic intervention from the government is crucial considering the economic, cultural, social, and historical significance of the crop to the society and the country at large.